Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1161/01.res.76.2.305
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide–Generating Compounds Inhibit Total Protein and Collagen Synthesis in Cultured Vascular Smooth Muscle Cells

Abstract: Nitric oxide (NO) participates in the regulation of vascular tone and smooth muscle cell proliferation, but little is known of its effect on total protein and matrix synthesis in smooth muscle. We studied the effects of the NO-generating compounds S-nitroso-N-acetylpenicillamine (SNAP, 0.4 to 1.2 mmol/L) and sodium nitroprusside (SNP, 0.1 to 0.5 mmol/L) on total protein (using [3H]leucine) and collagen (using [3H]proline) synthesis in cultured rabbit aortic smooth muscle cells. Both agents caused dose-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
125
2
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(137 citation statements)
references
References 21 publications
7
125
2
2
Order By: Relevance
“…Previous experiments have demonstrated that NO donors added directly to the VSMC growth medium decreased collagen I concentrations, but not collagen III concentrations. 21 Kolpakov et al 22 have also previously found that NO inhibits total protein and collagen synthesis in noncoronary VSMCs.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Previous experiments have demonstrated that NO donors added directly to the VSMC growth medium decreased collagen I concentrations, but not collagen III concentrations. 21 Kolpakov et al 22 have also previously found that NO inhibits total protein and collagen synthesis in noncoronary VSMCs.…”
Section: Discussionmentioning
confidence: 89%
“…Prior research has demonstrated that NO donors alter collagen metabolism when added directly to VSMCs 21,22 ; however, less is known with regard to the role of endogenously derived NO in vascular wall extracellular matrix metabolism. Since previous work has established that NO is produced by an endothelial constitutive enzyme, the experimental design employed a NOS antagonist to block endogenous synthesis of NO.…”
mentioning
confidence: 99%
“…There are reports that NO inhibits protein synthesis (40)(41)(42) at the level of translation initiation. Translation initiation depends mainly on the activity of eukaryotic initiation factors (eIFs).…”
Section: Discussionmentioning
confidence: 99%
“…23 Furthermore, expression of PDGF receptors is a consistent feature of the process of HSC activation in vitro and in vivo. 21,23 NO donors have been shown to reduce collagen type I deposition in vascular smooth muscle cells and in human HSCs, 24,25 and NO release induced by proinflammatory cytokines has been proven responsible for the inhibition of ␣-smooth muscle actin expression, a marker of HSC activation. 26 In addition, a possible direct antifibrogenic effect of NO donors is suggested by in vitro studies showing antiproliferative and antichemotactic actions of these compounds in vascular smooth muscle cells and glomerular mesangial cells.…”
Section: E Xperimental and Clinical Studies Have Indicated Thatmentioning
confidence: 99%